2017
DOI: 10.1007/s00167-017-4419-8
|View full text |Cite
|
Sign up to set email alerts
|

The angle of inclination of the native ACL in the coronal and sagittal planes

Abstract: Prognostic retrospective study, Level of evidence III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 22 publications
1
25
2
Order By: Relevance
“…In spite of having a significant difference between the coronal GIA in the AAMPT group (mean of 28.8±3.4°) and the MTTT group (mean of 23.76±5.64°), both the techniques place the graft in more inclination than native ACL which was found to be 15.72±4.75°. 29 MTTT in this study had GIA of 23.76° which is higher than the angle of the traditional TTT 5 , 21 , 30 , 31 and lies in-between the other modified TTT studies 22 , 32 , 38 (values presented in the literature, Figure 16 ).…”
Section: Discussioncontrasting
confidence: 41%
“…In spite of having a significant difference between the coronal GIA in the AAMPT group (mean of 28.8±3.4°) and the MTTT group (mean of 23.76±5.64°), both the techniques place the graft in more inclination than native ACL which was found to be 15.72±4.75°. 29 MTTT in this study had GIA of 23.76° which is higher than the angle of the traditional TTT 5 , 21 , 30 , 31 and lies in-between the other modified TTT studies 22 , 32 , 38 (values presented in the literature, Figure 16 ).…”
Section: Discussioncontrasting
confidence: 41%
“…Results showed an overall mean coronal angle of inclination of 63.4°, with the larger angle measuring 65.9° and the smaller angle measuring 60.7°. The overall ACL coronal angle average established in this study was slightly smaller than previously published coronal angles ranging from 65° to 76° (Ahn et al, 2016; Gentili et al, ; Illingworth et al, ; Kim et al, ; Reid et al, ). The ACL angle differences may be because of the variations in measurement techniques such as manual versus MRI studies, degree of knee flexion, or sample characteristics such as sex.…”
Section: Discussioncontrasting
confidence: 75%
“…One limitation of this study was the age of the cadavers (mean 76.5 ± 11.5 years), as the majority of ACL injuries occur to teenagers and young adults. Previous studies demonstrated differences in the coronal angle of inclination between skeletally immature and mature individuals (Kim et al, ; Reid et al, ). This variable was eliminated as only skeletally mature individuals were utilized.…”
Section: Discussionmentioning
confidence: 92%
“…Such information will also help to improve surgical treatments (eg, more accurate graft sizing and tunnel positioning) or to develop more relevant computer models for studying ACL biomechanics. This has motivated numerous investigations to study the age-related [21][22][23] or sex-dependent 24,25 differences in ACL morphology. A recent comprehensive review by Cone et al, 26 has provided summaries of the existing reports on a range of morphological features of the ACL.…”
mentioning
confidence: 99%